A glace at the importance of playing and the impact of technology use in relationships and plays during childhood (Research, Society and Development, 2020)
This study aims at identifying the contributions of playing to the child development, socialization and apprenticeship, and still, at understanding how technology has influenced human relationships and how this influence has impacted childhood and plays. It is intended to raise sensitize in parents, educators and Society concerning the playfulness that is being lived during childhood, being that playing not only a free time activity, but a learning act. Trough bibliographic research it is possible to understand the importance of playing. By playing, the child finds support for his/her physical, intellectual and social development, and yet, the development of identity and autonomy. The play is a means the kid inserts him/herself in society and culture, exploring the world and its possibilities. Nowadays, playing has been suffering changes. Currently, it is common that children replace traditional toys for the use of technology, and parents are also more and more inserted in the virtual world, what meaningfully interferes in the relationships between parents and children, making them far from each other and the living and dialogue lessen and lessen.  The indiscriminate use of technology deconstructs the affective bonds among the family members, collaborating for the lack of emotional reference in children.   Parents need to promote a harmonious living relationship and a healthy environment, in which the child can play and develop, with the attentive care and active and affective participation, effectively corroborating in the construction of their apprenticeship.